faktor faktor penentu kemenangan pasangan ridho yahya dan andriansyah fikri dalam pilkada kota prabumulih tahun 2013 - VOLINNATA, WINDU; ., FITRIYAH; ., SULISTYOWATI (Journal of Politic and Government Studies, 2016)
Diversity of the determinant factors of the triumph of the candidate encouraged to researchedof â€œ The Determinant Factors of the Triumph of Couple Candidate of Ridho Yahya andAndriansyah Fikri in Prabumulihâ€™sDirect Local Election in 2013â€. The desaign of thisresearch was qualitative descriptive with 99 respondents chosen by random sampling whichwas held in 2013.In 2013, Prabumulih rehold direct local election for the second that was to choose mayor andvice mayor during the period of 2013-2018 with 7 couples of candidate, and was winned byRidho Yahyaâ€“Andriansyah Fikri. This victory was determined by (a) sosiological factor (b)psychological factor (c) rational factor.The findings of this research is important for the political elite to study the dynamics andtendency of the voter behaviour. But, because of the method of this research was qualitative,so it will be a necessary for the further research to conduct quantitative research.Â Â Key Words : Direct local election, determinant factor of the triumph of candidate,personality factorÂ